An Introduction to Psychology - Murphy, Gardner, 1895-1979 (Culcutta Oxford Book Company, 1964)
Introduces contemporary psychology to the beginning student.
Include Graphs, Pictures, Glossary and Index
Keywords: Psychology -- Psychologie -- Étude et enseignement